Comparative Study on Different Structural Forms of Telecommunication Towers - Kiriparan, B.; Janusan, J.; Jayasinghe, J.A.S.C.; Dissanayake, U.I. (Society of Structural Engineers, SriLanka, 2023)
Telecommunication infrastructures plays a key role in providing telecommunication service. The rapid increase in usage of telecommunication devices during the recent past created necessity for construction of new telecommunication structures and upgrading of existing structures to meet the increased demand. Ground based towers, monopoles and guy mast structures are three commonly used structural forms of telecommunication towers. The factors such as land usage for the infrastructure, cost, material usage, structural performance, space available for connection of antennas and constructability to be critically considered during the preliminary design to select most suitable structural form. This study investigates the trend in variation of above-mentioned parameters for different structural forms based on the data collected from 31 telecommunication towers designed by the author in Sri Lanka. The results presented in the form of graphs provide useful information for structural engineers and other decision makers in the telecommunication infrastructure development sector in the selection of a most feasible structural form for the telecommunication structure according to the project constrains. Further, the comparison of lateral stiffness, material usage and the exposed surface area against wind loading for different bracing configurations commonly used for rectangular based telecommunication towers were presented. These results will be useful for structural engineers to select optimum bracing configurations based on the extent of wind loading.
Keywords: Telecommunication towers; Monopoles; Guy mast; Preliminary design